الكلمة المنطوقة ودورها في بناء المكانة الذهنية ) دراسة تحليلية الراء عينة من المستفيدين في المستشفيات الخاصه في مدينة أربيل ( - Mahabat Noori Abdo; Nihayat Saady Rahman; Razaw Abdulkhaliq Hussien (QALAAI ZANIST SCIENTIFIC JOURNAL, 2019)
The word of mouth and its role in building mental status The study of analytical of samle opinion of benefical personnel in hospital private in the city of Erbil The search seeks to identify the word of mouth by its samples (credibility of the word, the content of the word, the source of the word) and its role in building the mental position. A numbers of private hospital were tested in the city of Erbil. The research problem was determined by asking questions about the nature of the relationship and the effect between the variables. A hypothesis was designed to reflect the main hypotheses. The questionnaire was used as a means of obtaining data. It was distributed to a random sample of (260) the beneficiaries in this hospital, the research retrieved (250) form and all were valid for analysis. In order to ensure the validity of the silverware for multiple tests through the use of the program (SPSSv.20), And applied descriptive analytical research. The research reached a period of conclusions, the most important of which is the existence of a relationship and a guided effect between the two research variables.